The Influence of Discipline, Speed and Responsiveness of Office boy Work on Work Productivity at PT. Astra International Tbk, Bengkulu Branch - Meylinda Meylinda; Tezar Arianto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to determine the Effect of Discipline, Speed , and Responsiveness of Work Office Boys on Work Productivity at PT. Astra International, Tbk. Bengkulu Branch, either partially or simultaneously. Respondents in this study were employees at PT. Astra International, Tbk. Bengkulu branch, totaling 68 people. In this research, the writer uses the method of collecting data by means of observation, distributing questionnaires, or questionnaires. Data analysis techniques used in this study, using instrument test, classical assumption test, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. So it can be concluded that the Discipline, Speed and Responsiveness of Work Office boy have a positive and significant effect partially or simultaneously on Work Productivity at PT. Astra International, Tbk. Bengkulu Branch.